Kajian Sejarah Periodisasi Perkembangan Ushul Fiqh - Mochamad Ariel Ferdiansyah; Luqyana Lutfi Hana; Hanif Nasrul Aziz; Salwa Zakia; Zahwa Amalia Nisa’; M. Imamul Muttaqin (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This article discusses the development of the periodization of ushul fiqh starting from the time of the Prophet, the companions, the tabi'in, the 4 Imams of madzhab, to the muta'akhirin period. This article was written to overcome the misunderstanding of Muslims today. The research method used in this research is library research, by collecting various existing literature. Ushul fiqh is the science of establishing a law using sources from the Koran and Sunnah. Ushul fiqh first existed during the time of the Prophet, precisely when he was first sent. At that time ushul fiqh was only limited to the interpretation of the Al-Qur'an and hadith from the Prophet. As time goes by, the methods used in ushul fiqh also develop. Moreover, in contemporary times, methods for determining laws are increasingly increasing and developing following various new problems that arise.